Possible Involvement of Foxp3+ Regulatory T Cells in the Development of Immune-Mediated Pancreatitis in MRL/Mp Mice Treated with Polyinosinic:Polycytidylic Acid. (26th May 2013) - Koyabu, Masanori; Uchida, Kazushige; Sakaguchi, Yutaku; Fukata, Norimasa; Kusuda, Takeo; Miyoshi, Hideaki; Yoshida, Katsunori; Sumimoto, Kimi; Mitsuyama, Toshiyuki; Fukui, Toshiro; Nishio, Akiyoshi; Okazaki, Kazuichi
Abstract : Objectives . This study was conducted to clarify whether or not Tregs are involved in the development of immune-mediated pancreatitis in MRL/Mp mice as an AIP (autoimmune pancreatitis) model, in order to understand more clearly the pathogenic mechanism of AIP. Methods . We compared the immunohistochemical features of pancreatic forkhead box P3 (Foxp3) in the administration of poly I:C in MRL/Mp mice and two types of control mice (BALB/c and C57BL/6). As a contrast, we analyzed three mouse models of pancreatitis without autoimmune mechanism (Cerulein-, Ligation-, and Ligation + Cerulein-treated mice). After staining these specimens, we compared the ratios of Foxp3-positive cells to infiltrated mononuclear cells (Foxp3/Mono). Results . Our immunohistochemical study of Foxp3 revealed that the infiltration of Foxp3-positive cells increased in poly I:C-treated MRL/Mp mice. The histopathological score of pancreatitis showed no difference among poly I:C-treated MRL/Mp, Ligation-, and Ligation + Cerulein-treated mice; however, the Foxp3/Mono ratio in poly I:C-treated MRL/Mp mice was significantly increased compared with Ligation- and Ligation + Cerulein-treated mice. Conclusions . MRL/Mp mice treated with poly I:C showed early development of pancreatitis with abundant infiltration of Foxp3-positive cells. There may be a possibility that Tregs are involved in the development of pancreatitis in these mice.